A NICE Delivery—The Cross-Atlantic Divide Over Treatment Intensity in Childbirth. Issue 2 (June 2016) - Shah, N.
Abstract : ( N Engl J Med. 2015;372(23):2181–2183) This editorial examines the transatlantic debate over best labor and delivery practices for healthy women that arose following the results of an evidence-based review that prompted the United Kingdom's National Institute for Health and Care Excellence (NICE) to conclude that it is safer for healthy women with straightforward pregnancies to give birth at home or in a midwife-led unit than in a hospital under the supervision of an obstetrician.